Determinants of profitability before and after goods and services tax (GST) / Harith Zulqarnain Mahat - Mahat, Harith Zulqarnain (Faculty of Business Management, University Teknologi MARA, 2017)
This study is to explore the impact of determinants towards the profitability of Malaysian Companies before and after the implementation of Goods and Services Tax (GST). The company specifics determinants are used to determine the company profitability while the dependent variable that used is return on assets (ROA) to measure the company profitability. The specifics determinants are size, liquidity, leverage, sales growth and corporate tax. This study uses a sample of 15 companies listed in Bursa Malaysia for over the period 2013 to 2016. All companies that implementing GST are included as the sample except financial-based companies because their nature of reporting business is different from the ordinary sectors. The data are analysed using Ordinary Least Square (OLS). The findings shows that the liquidity, leverage and corporate tax have a positive impact towards the firms' profitability. It indicates that highly liquid companies, increase in debt and increase in tax towards the companies' net income will have more profits. While size and sales growth were found as insignificant in predicting the dependent variable. With the implementation of GST, there is some issues related to the process of sorting out the interaction between the GST rules and the operational issues. It is an on-going process that will take time and effort. Changes to the rules and policies will be on-going due to the shifting business situation. The implementation ofthe GST and a number of issues have not been sorted out because the industry is quite complex. The approaches of GST that implemented are vary for every different industries and this unsorted out issues are making things more complex. This issues led to the difficulty of the companies to determine their current profitability as the process of preparing their financial statements becoming more complex and tough.